Pentingnya Perspektif Orang Tua Pada Implementasi Kurikulum Merdeka Sekolah Dasar di Kota Yogyakarta - Abidin, Muhammad Zainal; Widiyawanti, Widiyawanti (TADRUSUUN: JURNAL PENDIDIKAN DASAR, 2025)
This study is a qualitative study with a narrative type. It aims to describe and analyze the perspectives of parents of elementary school students on the implementation of the Independent Curriculum in the city of Yogyakarta. The data collected are in the form of stories or narratives through semi-structured interviews with parents of students who are the heads of school committees and parents of students who are not members of the committee. The stories or narratives collected are then analyzed and linked to the support of relevant literature and theories to obtain meaning. The results of the study show that the perspectives of parents of elementary school students on the implementation of the Independent Curriculum in the city of Yogyakarta are diverse. However, these perspectives tend to be less in accordance with the essence of learning in the Independent Curriculum which has a constructivist paradigm. Parents of elementary school students still believe that the traditional learning paradigm is the best for elementary school students. In fact, the Independent Curriculum aims to place children as active subjects in learning and prioritize children's talents and interests. So researchers can conclude and provide recommendations that the perspective of parents is very important to consider in the process of implementing a curriculum. The perspective of parents needs to be built so that they can become partners of teachers and schools in monitoring, supporting and directing children's potential.